Study on Physical Quality of Milk of Peranakan Ettawa Goat using Different Pasteurization Methods - Sulmiyati Sulmiyati; Najmah Ali; Marsudi Marsudi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
Goat milk is a liquid medium having a very complete composition, but it can not last long when stored at room temperature. Milk stored at room temperature can be easily spoiled if it does not receive special treatment such as pasteurization. The purpose of this study was to obtain the right temperature and time in the processing of pasteurized milk. The experiment was carried out according to completely randomized design consisted of 3 treatments and 5 replications. The treatments of this research were the method of pasteurization , i.e. A1 = LTLT (Low Temperature Long Time, temperature of 65oC for 30 minutes) A2 = HTST (High Temperature Short Time, temperature of 75oC for 30 seconds) and A3 = Pasteurization UHT (temperature of 81oC for 30 minutes). The observed parameters were color, smell, taste, gravity weight, pH, acidity and the reductase score. The results of the study showed that different pasteurization methods had no significant effects (P>0.05) on the color, smell and taste of the goat milk, but significantly affected (P <0.05) gravity weight and lactic acid percentage. Similarly, the treatments did not have significant effects (P>0.05) on the reductase score of pasteurized goat milk.